Kualitas Pelayanan Administrasi Terpadu (Paten) Di Kecamatan Rengasdengklok - Kadam, Elia; Kurniansyah, Dadan; Santoso, Made Panji Teguh (Jurnal Ilmiah Wahana Pendidikan, 2024)
In order to guarantee quality public services, the government announced in Permendagri No. 4 of 2010 that every sub-district needs to be used as the main communication hub in the region in order to increase the quality and reduce the quantity of public services. provided to residents. The quality of public services in the regions must be increased to a higher level. Compared to services that are based on the information provided by the organizers, local communities have more resources to get the best possible service. For this reason, the Government established a PATEN in Rengasdengklok District. The purpose of this PATEN is to improve the quality of service and improve service to the community and minimize the provision of services in a convoluted manner.